Initial characterization of the ferric iron transport system of Corynebacterium diphtheriae. - Russell, L M (1983)
Transport of ferric iron into Corynebacterium diphtheriae C7(beta) was shown to occur by a high-affinity, active transport system. Optimal rates were at pH 6.8 and 40 degrees C. Strong inhibition of uptake by carbonyl cyanide m-chlorophenylhydrazone was consistent with the electrochemical proton gradient as the major energy source for iron transport, and inhibition by Hg2+ indicated that sulfhydryl groups were also important. Evidence was obtained for stimulation of iron uptake at pH 8.0 by a dialyzable, extracellular factor present in conditioned medium from low-iron cultures of C. diphtheriae.